Predictive validity of PRISMA-7 as a screening instrument for frailty in a hospital setting. Issue 10 (28th October 2020) - Hoffmann, Sarah; Wiben, Amalie; Kruse, Marie; Jacobsen, Katja Kemp; Lembeck, Maurice A; Holm, Ellen Astrid
Abstract : Objectives: Frailty is a major clinical geriatric syndrome associated with serious adverse events including functional disability, falls, hospitalisation, increased morbidity and mortality. The aim of this study was to study the associations between frailty defined as Program of Research to Integrate Services for the Maintenance of Autonomy (PRISMA-7) score ≥3 and use of healthcare resources in hospital and in the municipality as well as association between frailty and mortality. Design: Register-based retrospective study. Setting: The target population consists of patients aged 75 years or above who, during hospital stay, were assessed by a physiotherapist, and at discharge from hospital were prescribed further physical training in the community. Participants: 973 individuals aged 75+ years were included. Outcome measures: We examined associations between frailty and use of healthcare resources in hospital and in the municipality as well as the association between frailty and mortality. Results: 973 individuals aged 75+ years were included. Of these, 63.9% had a PRISMA-7 score ≥3 and were thus defined as frail. Frail individuals were older compared with non-frail with mean ages of 84.6 and 80.4 years, respectively, p>0.001. Age and gender-adjusted mortality after 1 year was higher among the frail (OR 2.46, 95% CI 1.53 to 3.97). Use of healthcare services in the municipality as well as hospital admissions was significantly higher among frail individuals. Conclusions: Based on these findings we consider PRISMA-7 to be useful in an in-hospital setting as a screening tool to identify frail elderly patients who may profit from further geriatric assessment during hospital stay. Trial registration number: ID REG-070-2017.